Thermal Degradation Characteristics of Rapeseed Biodiesel And Its Blends With Petroleum Diesel. Issue 9 (30th May 2020) - Li, Hui; Liu, Fengsheng; Zhou, Shoujun; Liu, Jiying; Wu, Zhongjie
Abstract: Biodiesel is always blended with petroleum diesel to serve as the transport fuel, to obtain the specific impact of petroleum diesel addition on thermal degradation for biodiesel; in this study, the thermal degradation characteristics of biodiesel and biodiesel blends with diesel are investigated by thermogravimetric analysis at heating rates of 10, 15, and 20 K min −1 in the temperature range of 298 to 873 K. The kinetic parameters of activation energy are calculated based on the iso-conversional method, namely the Friedman method and Flynn–Wall–Ozawa method, and the reaction order is determined by Avrami theory. In addition, the thermodynamic parameters of enthalpy, entropy, and Gibbs-free energy are also calculated.